Socio-Economic Factors Influencing the Adoption of Linking Smallholder Farmers to the Market (LinkSFarM) Project by Vegetable Farmers in Malungon, Sarangani - Carriedo, Kristine Joy Calinawan; Balogbog, Keno Jay M. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the socio-economic factors influencing the adoption of the Linking Smallholder Farmers to Markets (LinkSFarM) project among vegetable farmers in Malungon, Sarangani. Specifically, it aimed to assess the farmers’ demographic and farm profiles, economic status, marketing practices, awareness and perception of the project, as well as the challenges encountered during its implementation. A mixed-methods approach was employed, combining quantitative and qualitative techniques, with data gathered from 86 farmer beneficiaries from three barangays. Quantitative data were analyzed using tabular presentations to show frequencies, percentages, and rankings, to clearly identify which categories ranked highest or lowest. For the qualitative component, responses were transcribed one by one, with codes for every participant to maintain anonymity. Thematic analysis was then conducted to extract key themes and sub-themes, offering deeper insights into the challenges faced by farmers and their organizations. Combining both methods is crucial, since the quantitative data gives actual evidence of trends and relationships, and the qualitative data provides deeper context and understanding of farmers’ perceptions, and experiences. This provides a more comprehensive understanding of the factors that influence adoption of LinksFarM project. Results show that while the LinkSFarM project provides a promising benefit to the farmer such as increased welfare and income. However, despite the potential benefit of the project, several challenges were encountered during the implementation. These include financial constraints, market access, membership in farmers' organizations, infrastructure, and knowledge gaps. Both quantitative and qualitative findings highlight financial constraints as